Donor Darah Sebagai Upaya Bakti Sosial Mahasiswa Guna Kebutuhan Masyarakat Kabupaten Pasuruan - Mohammad Naufal Al Farochi; Yonika Nazla Rohma; Maulida Nur Fadhilah; Arif Rachman Putra; Mujito Mujito; Suwito Suwito; Rommy Hardyansah; Didit Darmawan; Moh Syaiful Anwar (Universitas Maritim AMNI Semarang, 2025)
The main issue faced by the community in Pasuruan Regency is the shortage of a safe and adequate blood supply, especially for urgent needs such as accidents, surgeries, or certain illnesses. The Blood Donation Program initiated by students serves as a form of social service aimed at supporting blood stock availability and raising community awareness on the importance of blood donation. The method of implementation includes outreach to students and local residents, and collaboration with the local Red Cross Blood Transfusion Unit (UTD PMI) to ensure strict health standards. Activities include direct blood donation, involving students and residents as volunteer donors. The outcome of this initiative is a significant increase in blood stock for the UTD PMI in Pasuruan Regency, along with a boost in community participation and understanding of the humanitarian value of blood donation as an essential social contribution.